2019
DOI: 10.1016/j.nicl.2019.101741
|View full text |Cite
|
Sign up to set email alerts
|

Physiological significance of R-fMRI indices: Can functional metrics differentiate structural lesions (brain tumors)?

Abstract: Resting-state functional MRI (R-fMRI) research has recently entered the era of “big data”, however, few studies have provided a rigorous validation of the physiological underpinnings of R-fMRI indices. Although studies have reported that various neuropsychiatric disorders exhibit abnormalities in R-fMRI measures, these “biomarkers” have not been validated in differentiating structural lesions (brain tumors) as a concept proof. We enrolled 60 patients with intracranial tumors located in the unilateral cranialca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…The third limitation is the sample size of our study. Much larger sample size is needed for between-subject designs than within-subject designs to detect an effect (Fan et al, 2019). Thus, null results in comparing MDD patients before treatment and HCs could be due to this design difference.…”
Section: Discussionmentioning
confidence: 99%
“…The third limitation is the sample size of our study. Much larger sample size is needed for between-subject designs than within-subject designs to detect an effect (Fan et al, 2019). Thus, null results in comparing MDD patients before treatment and HCs could be due to this design difference.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have evaluated abnormal brain activity in patients with diabetic neuropathy treated with acupuncture using ALFF, ReHo and FC yet these studies have reported inconclusive findings. [24][25][26][27][28] Moreover, previous studies on acupuncture for PDPN have been focused on changes in the spinal level rather than the central level due to the limitations of research techniques. Recently, rapid developments in rs-fMRI technology have allowed it to be widely used to investigate changes in brain function changes in a variety of diseases.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%